FENOMENOLOGI FITUA (TASAWUF) DALAM PRESPEKTIF PENDIDIKAN ISLAM PADA MASYARAKAT BIMA - Abdul Salam (Prodi PAI STIT Sunan Giri Bima, 2023)
Fitua phenomenology (tasawuf) has such an important meaning in the Bima community, it is known as the old recitation or called tasawuf for the elders. It contains pata ruma (knowing Allah SWT), knowing one's true self (Pata Weki). Phenomenology of Fitua (tasawuf) from the perspective of Islamic education in the Bima community, namely what is known as the old Koran or its fitua. So that the old Koran is almost lost among the Bima community. In fact, this old Koran is only found among the elderly who really study the three sciences, namely fiqh, usul and tasawuf. So fitua can contain several elements that can be interpreted by the author, including; Revealing the phenomenology of Sufism models that existed in Bima in the past; Revealing the phenomenology of fitua (tasawuf) from the perspective of Islamic Education in the present-day Bima society.